Natural hybridization between divergent lineages in a selfing hermaphroditic fish. (13th June 2018) - Tatarenkov, Andrey; Earley, Ryan L.; Taylor, D. Scott; Davis, William P.; Avise, John C.
Abstract : By definition, mating between individuals is infrequent in highly selfing organisms, and so too, therefore, hybridization should be rare between genetically divergent lineages in predominantly self-fertilizing species. Notwithstanding these expectations, here we report a remarkable case of natural hybridization between highly diverged phylogeographic lineages of the mangrove rivulus, a small killifish that reproduces predominantly by self-fertilization and typically is found as highly homozygous lines in most parts of its extensive geographical range. Two distinctive genetic lineages ( Kryptolebias marmoratus and a 'Central clade' closely related to K. hermaphroditus ) previously were not known in sympatry, but were found by us to co-occur on San Salvador, Bahamas. Genetic analyses of a mitochondrial and multiple nuclear markers determined the direction of a cross producing a hybrid fish. Furthermore, we show that this hybrid individual was viable, as it successfully reproduced by self-fertilization for two generations. Additional sampling of this population will be necessary to determine if backcrossing of hybrids to the parental lineages occurs in nature and to analyse whether such backcross progeny are viable. Application of the biological species concept (BSC) is traditionally difficult in clonally reproducing organisms. Our results show that although mangrove rivulus fish are mostly highly selfing in nature (resulting in isogenic, effectively clonal and homozygous progeny), classification within this taxonomic complex need not be incompatible with the BSC.